THE EFFECT OF URTI ON THE INCIDENCE OF ACUTE OTITIS MEDIA IN CHILDREN AGED 0-5 YEARS AT THE ENT POLYCLINIC OF PHC HOSPITAL SURABAYA - Cantika, Cinta; Hadi, Wiyono; Waworuntu, Gladdy Lysias (JURNAL WIDYA MEDIKA, 2025)
Upper respiratory tract infection (URTI) is an acute infection that affects the nose, paranasal sinuses, tonsils, pharynx, and larynx. It is commonly found in children under the age of 5. One of the most frequent and concerning complications of URTI in children is acute otitis media (AOM), a middle ear infection that can negatively impact a child’s health. Understanding the relationship between URTI and AOM is important to enable early prevention and treatment. This study aims to examine the effect of URTI on the incidence of AOM in children aged 0–5 years at the ENT Polyclinic of PHC Hospital Surabaya. This research employs an observational analytic design using a cross-sectional method with non-probability purposive sampling. Data were collected from medical records of pediatric patients aged 0–5 years who visited the ENT Polyclinic between January and December 2022. The data were analyzed using the contingency coefficient test, and a result was considered statistically significant if p < 0.05. Out of 45 patients who met the study criteria, the average age was 2.82 years. There were more males (62%) than females (38%). A total of 19 children (42%) had both URTI and AOM, 6 children (13%) had AOM without URTI, and 20 children (44%) had URTI without AOM. The analysis showed a p-value of 0.019 and a contingency coefficient of 0.331, indicating a moderate association between URTI and AOM. URTI has a significant influence on the incidence of acute otitis media in children aged 0–5 years at the ENT Polyclinic of PHC Hospital Surabaya.